Minimally Invasive Methods Of Treatment Of Patients With Acute Cholecystitis - Saydullaev Zainiddin Yakhshiboevich; Davlatov Salim Sulaymanovich (Genius Journals, 2024)
Acute cholecystitis remains an urgent problem of modern emergency surgery. The incidence of acute cholecystitis still remains at a high level - 20-25% of patients in surgical departments. The number of destructive forms of the disease in older patients often exceeds 40%. The level of postoperative lethality in this category of patients remains high and reaches 20% during operations at the height of an attack, and in the presence of severe concomitant pathology postoperative lethality exceeds 40-50%. However, in case of delayed or planned surgical intervention after additional examination of patients and correction of concomitant diseases the level of postoperative lethality can be significantly reduced - it does not exceed 0.5-1%
Keywords: Acute cholecystitis; minimally invasive; treatment methods